Repeated exposure of epithelial cells to apoptotic cells induces the specific selection of an adaptive phenotype: Implications for tumorigenesis - Feng, Lanfei (J Biol Chem, 2018)
The consequences of apoptosis extend beyond the mere death of the cell. We have shown that receptor-mediated recognition of apoptotic target cells by viable kidney proximal tubular epithelial cells (PTECs) inhibits PTEC proliferation, growth, and survival. Here, we tested the hypothesis that continual exposure to apoptotic targets can induce a phenotypic change in responding PTECs, as in other instances of natural selection. In particular, we demonstrate that repeated exposure to apoptotic targets leads to emergence of a PTEC line (denoted BU.MPT(SEL)) resistant to apoptotic target–induced death. Resistance is exquisitely specific. Not only are BU.MPT(SEL) responders fully resistant to apoptotic target–induced death (∼85% survival versus <10% survival of nonselected cells) but do so while retaining sensitivity to all other target-induced responses, including inhibition of proliferation and growth. Moreover, the resistance of BU.MPT(SEL) responders is specific to target-induced apoptosis, as apoptosis in response to other suicidal stimuli occurs normally. Comparison of the signaling events induced by apoptotic target exposure in selected versus nonselected responders indicated that the acquired resistance of BU.MPT(SEL) cells lies in a regulatory step affecting the generation of the pro-apoptotic protein, truncated BH3 interacting–domain death agonist (tBID), most likely at the level of BID cleavage by caspase-8. This specific adaptation has especial relevance for cancer, in which the prominence and persistence of cell death entail magnification of the post-mortem effects of apoptotic cells. Just as cancer cells acquire specific resistance to chemotherapeutic agents, we propose that cancer cells may also adapt to their ongoing exposure to apoptotic targets.